2016
DOI: 10.3892/ol.2016.4209
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standardized flow cytometric method to conduct longitudinal analyses of intracellular CD3ζ expression in patients with head and neck cancer

Abstract: Abstract. Head and neck squamous cell carcinoma (HNSCC) is the sixth most common neoplasm in the world. The follow-up protocols currently available do not appear to diagnose treatment failures and recurrences early enough to provide the best treatment to improve the survival rates of patients. The identification of biomarkers may aid in diagnosing, monitoring the progression, or predicting treatment outcomes in HNSCC. The present study aimed to evaluate whether cluster of differentiation (CD) 3ζ chain expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
2
8
1
Order By: Relevance
“…). This finding was in agreement with the previous reports of poor CD3ζ expression by us and others . This also suggests that there is no quantitative difference in the proportion of T cell subsets in PBMC of HNSCC and healthy controls but a qualitative difference between the T cells of the two groups.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…). This finding was in agreement with the previous reports of poor CD3ζ expression by us and others . This also suggests that there is no quantitative difference in the proportion of T cell subsets in PBMC of HNSCC and healthy controls but a qualitative difference between the T cells of the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…These include: spontaneous apoptosis of circulating T cells, poor expression of co‐stimulatory molecules and loss of HLA class I molecules on tumor cell surface, a decrease in the absolute cell counts of specific T cell subsets, predominant Th2 responses, 31–34 production of immunosuppressive factors by tumors, T cell exhaustion, over‐expression of regulatory T cells and dysfunctional/inhibitory dendritic cells . Earlier publications from our group and others have reported reduced levels of CD3ζ‐chain in both tumor infiltrating lymphocytes and peripheral blood lymphocytes probably due to inhibitory factors, transcriptional defects and production of Arginase I in the tumor microenvironment by myeloid cells . We did not observe any statistical differences in proportion of CD3 ε+ T‐cell subset in the PBMC of the HNSCC patients and the healthy controls, however, the relative MFI of the CD3ζ expression in the T cells of the HNSCC patients was significantly lower than that of the healthy controls.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…CCK-8 assay is a commonly used assay to evaluate the cytotoxic activity of chemical constituents against cancer cells (11). Flow cytometry analysis is a commonly used assay to explore whether the cytotoxic activity of chemical constituents against cancer cells is associated with apoptosis (12). The results of CCK-8 and flow cytometry assays in the present study suggested that chrysotoxene demonstrated cytotoxic activity against HepG2 cells and the cytotoxic activity may be induced by apoptosis (Figs.…”
Section: Discussionsupporting
confidence: 49%